A Modified Gravitational Search Algorithm for Discrete Optimization Problem - Zuwairie, Ibrahim; Zulkifli, Md. Yusof; Shahdan, Sudin; Sophan Wahyudi, Nawawi; Amar Faiz, Zainal Abidin; Muhammad Arif, Abdul Rahim; Kamal, Khalil (United Kingdom Simulation Society, 2014)
This paper presents a modified Gravitational Search Algorithm (GSA) called Discrete Gravitational Search Algorithm (DGSA) for discrete optimization problems. In DGSA, an agent’s position is updated based on its direction and velocity. Both the direction and velocity determine the candidates of integer values for the position update of an agent and then the selection is done randomly. Unimodal test functions are used to evaluate the performance of the proposed DGSA. The experimental result shows that the FDGSA able to find better solutions and converges faster compared to the Binary Gravitational Search Algorithm.